2019
DOI: 10.4149/bll_2019_008
|View full text |Cite
|
Sign up to set email alerts
|

Volume regulation of muscle cells in the carp Cyprinus carpio in response to hypernatremia

Abstract: BACKGROUND: Hypernatremia supports the movement of water from the intracellular to the intercellular space. This shift leads to cells shrinkage and disruption of intracellular processes, representing risk factors of morbidity and mortality in clinical circumstances. On the other hand, hypernatremia triggers protective mechanisms that counteract damage of cells. OBJECTIVES: To determine in experiments in vivo the ranges of sodium content regulation in the blood plasma of carp characterizing the norm and hyperna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Goldfi sh tolerates water salinity to 6.0 g/L without pronounced signs of stress (29). At water salinity in the range of 8.0-10.0 g/L and up to the upper limit of tolerable salinity (CS), the concentration of Na + in the plasma of goldfi sh and other freshwater Teleostei rises from ~ 150 to 200 mmol/kg, the level of cortisol in the blood is elevated, signs of muscle dehydration appear, along with a decreased locomotor activity and growth rates, decreased urine volume, and increased water consumption (18,19,20,21,27,28,29,30,31,32,33).…”
Section: Comparison Of Water-salt Homeostasis Parameters In the Body ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Goldfi sh tolerates water salinity to 6.0 g/L without pronounced signs of stress (29). At water salinity in the range of 8.0-10.0 g/L and up to the upper limit of tolerable salinity (CS), the concentration of Na + in the plasma of goldfi sh and other freshwater Teleostei rises from ~ 150 to 200 mmol/kg, the level of cortisol in the blood is elevated, signs of muscle dehydration appear, along with a decreased locomotor activity and growth rates, decreased urine volume, and increased water consumption (18,19,20,21,27,28,29,30,31,32,33).…”
Section: Comparison Of Water-salt Homeostasis Parameters In the Body ...mentioning
confidence: 99%
“…The range of plasma sodium concentration in freshwater teleosts is comparable to that of mammals (18,19). In the conditions of extremely high critical water salinity (CS) tolerated by fi sh, the sodium concentration in their plasma increases to ~190 -206 mmol/kg (10,18,20).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the summarized data, it has been demonstrated that the concentration of sodium in the blood plasma of healthy people is maintained within the range of 130-145 mmol/L (3). With regard to the norm, the concentration of sodium in the blood plasma of hospitalized patients decreased to 110 mmol/L (8), 108 mmol/L (6,9), 106 mmol/L (5), 104 mmol/L (7), 98 mmol/L (4), 96 mmol/L (19), or 93 mmol/L (13).…”
Section: The Humansmentioning
confidence: 99%